PENGEMBANGAN PERENCANAAN PEMBELAJARAN BERBICARA DENGAN PROSEDUR KOMPLEKS MENGGUNAKAN MEDIA VLOG SISWA KELAS X SMA NEGERI 14 SAMARINDA - Irda Polina (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
This study aims to (1) create a lesson plan (RPP) from the development of speaking lesson plan using complex procedures on vlogs of 10th grade high school students; (2) develop speaking materials using complex procedures on vlogs based on the students’ needs; (3) develop the evaluation of speaking using complex procedures on the students’ vlogs. It applies research and development (RD) of Borg and Gall development model. The population in this research is 31 students of SMA Negeri 14 Samarinda. They are 10th graders. Trials are conducted in two stages: small group and large group or field trials. The data collection techniques used is observation, interview, and tests. It uses descriptive and qualitative analysis technique.